PEMANFAATAN DAUN SEKITAR SEBAGAI MOTIF PADA KAIN DI SDN 24 MATARAM - Novia Dian Rahmadani; Mareta Olivia; Nanda Faridatul Aulia; Reza Nurizzaty; Ni Ketut Satialini Pujiyantari; Lalu Wira Zain Amrullah (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
Indonesia has abundant biodiversity, thus providing great potential to utilize natural materials such as leaves as motifs in textile art through ecoprint techniques. This community service aims to describe the use of leaves found around the school environment as ecoprint motifs on fabrics at SDN 24 Mataram. This community service uses a training approach so that students are directly involved in ecoprint making activities. The ecoprint process includes leaf selection, arrangement on fabric, printing through pressure and evaporation, and color fixation using natural mordants. The results of the community service show that various leaves available around the school can be used effectively to produce ecoprint motifs with varying levels of clarity and color intensity. The success of the motif is influenced by leaf thickness, leaf vein structure, printing technique, fixation process, and heating method. In addition, ecoprint activities provide positive educational benefits by increasing students' creativity, observation skills, and environmental awareness. Thus, the use of surrounding leaves as ecoprint motifs can function as a creative, contextual, and environmentally friendly activity in elementary schools.